All-fiber three-wavelength laser for functional photoacoustic microscopy - Mingxuan Yang; Zheng Qu; Mohammadreza Amjadian; Xu Tang; Jiangbo Chen; Lidai Wang (Photoacoustics)
Advanced multi-wavelength pulsed laser is a key technique for functional optical-resolution photoacoustic microscopy (OR-PAM). By utilizing the stimulated Raman scattering (SRS) effect, we can generate various wavelengths from a single-wavelength pump laser, offering a simple and cost-effective solution for OR-PAM. However, existing multi-wavelength SRS lasers typically require fine alignment of many free-space optical components with single-mode fibers, which are susceptible to mechanical disturbances and temperature fluctuations, leading to high maintenance costs. To address this challenge, we develop an all-fiber three-wavelength SRS laser source for functional OR-PAM. A pump laser beam is launched into an optical fiber network, which splits and delays these laser pulses and generates different optical wavelengths in different fiber branches, and then merges them at the output end of the fiber network. This approach requires only one instance of fiber launching, dramatically simplifying the alignment and improving the laser stability. Using a decoding algorithm, we can separate the PA signals from different optical wavelengths and then calculate oxygen saturation (sO2) and flow speed. The SRS fiber network provides stable energy ratios among different optical wavelengths during long-time operation. We use the all-fiber OR-PAM system to monitor the brain function for four hours, demonstrating exceptional stability in functional imaging. The small size, simple structure, and low cost make it suitable for many preclinical and clinical applications.